Prognosis of Early-Stage Hepatocellular Carcinoma: Comparison between Trans-Arterial Chemoembolization and Radiofrequency Ablation - Yun, Byung-Yoon (Cancers (Basel), 2020)
SIMPLE SUMMARY: Radiofrequency ablation (RFA) is a curative treatment for early-stage hepatocellular carcinoma (HCC) ineligible for surgery or liver transplantation. However, trans-arterial chemoembolization (TACE) might be an alternative when RFA is contraindicated due to structural problems. Among treatment-naive HCC patients fulfilling the Milan criteria who underwent RFA (n = 136) or TACE (n = 268), complete response (CR) and 5-year recurrence-free survival (RFS) rates were higher in the RFA group than in the TACE group (94.1% vs. 71.6% and 35.8% vs. 17.0%, respectively; both p < 0.001), whereas 5-year overall survival (OS) rates were not significantly different (65.5% vs. 72.3%, respectively; p = 0.100). After propensity-score matching, similar results were also reproduced. Hence, TACE could be an effective alternative to RFA in terms of OS rates. However, TACE should be confined only to RFA-difficult cases, given its lower CR and RFS rates and multi-disciplinary approaches are desirable in decision-making. ABSTRACT: Radiofrequency ablation (RFA) is a curative treatment for early-stage hepatocellular carcinoma (HCC) ineligible for surgery or liver transplantation. However, trans-arterial chemoembolization (TACE) might be an alternative when RFA is contraindicated due to structural problems. Here, we aimed to compare their long-term outcomes. Treatment-naive HCC patients fulfilling the Milan criteria who underwent RFA (n = 136) or TACE (n = 268) were enrolled. Complete response (CR) and 5-year recurrence-free survival (RFS) rates were higher in the RFA group than in the TACE group (94.1% vs. 71.6% and 35.8% vs. 17.0%, respectively; both p < 0.001), whereas 5-year overall survival (OS) rates were not significantly different (65.5% vs. 72.3%, respectively; p = 0.100). Multivariate analysis showed that RFA was associated with better RFS (adjusted hazard ratio [aHR] 0.628; p = 0.001) than TACE, but not with better OS (aHR 1.325; p = 0.151). The most common 1st-line treatment after recurrence were TACE (n = 53), followed by RFA (n = 21) among the RFA group and TACE (n = 150), followed by RFA (n = 44) among the TACE group. After propensity-score matching, similar results were reproduced. Hence, TACE could be an effective alternative to RFA in terms of OS rates. However, TACE should be confined only to RFA-difficult cases, given its lower CR and RFS rates and multi-disciplinary approaches are desirable in decision-making.